Customer Validation for Startup - Cheryl Marlitta Stefia (Publikasi Indonesia, 2022)
Indonesia in 2020 is predicted to experience a demographic bonus. This generation is predicted to be more active in entrepreneurship because the protective nature of the millennial generation does not like attachments. Minister of Cooperatives and Small and Medium Enterprises (UKM) Anak Agung Gede Ngurah Puspayoga said the growth of entrepreneurship in Indonesia is increasing. The purpose of this study is to present Startup XYZ as a solution to these problems. Startup XYZ is a startup pioneer in Indonesia that offers online stall rental facilities that bring together stall providers and stall tenants. Present in answering complaints in the community, making it easier for customers with convenience, practicality, security, comfort for both stall providers and stall tenants. In addition, when users register as premium customers, users will get access to complete market analysis along with customer traffic data at each kiosk. This will make it easier for users to meet their target customers. The point that will be discussed is that every start-up needs to carry out a Customer Validation process. To analyze and examine the research methodology the author uses qualitative methods. Primary data was collected from the founders of Startup XYZ through interviews with 25 respondents. For the analysis technique, descriptive analysis was carried out. In order to be successful in building a start-up, the Customer Validation process plays an important role in the success of a startup, of course, with assumptions that match the assumptions of customer needs.